Web-Based Information System Design For Printing Services at CV.MRF Business Using Laravel Framework - Ramadhan, Adhitya; Aryono, Gagah Dwiki Putra; Masyhuri, Maman (INOVTEK Polbeng - Seri Informatika, 2025)
CV. MRF as a digital printing company, faces an operational crisis with a 23% monthly order error rate, 48-72-hour customer response time, and 15% potential customer loss due to a manual WhatsApp-spreadsheet system creating a 3.5-hour processing bottleneck per order, representing 78% of Indonesian printing SMEs. This research develops an innovative hybrid Waterfall methodology with integration checkpoints for the printing SME sector, creating a cost-effective digital transformation model with 180% ROI and 35% lower total cost of ownership than existing commercial solutions. Integrated Laravel system encompasses an automated workflow engine, dual authentication, real-time tracking, Midtrans payment gateway, and automated WhatsApp notifications. Black box testing results show a 100% success rate for 45 test cases with 83% operational efficiency improvement, processing time reduction from 30 minutes to 5 minutes, conversion rate increase from 65% to 92%, and 95% data accuracy. Scientific contribution produces a replicable methodology and performance metrics framework for 200+ similar printing businesses, providing benchmarking standards for the national printing sector digital transformation.